Feasibility of a Percutaneous and Non-Fluoroscopic Procedure for Transcatheter Mitral Valve Edge-to-Edge Repair - Shuyi Feng; Pengxu Kong; Shouzheng Wang; Fujian Duan; Fengwen Zhang; Yongquan Xie; Zefu Li; Wenchao Li; Xiangbin Pan (Reviews in Cardiovascular Medicine, 2023)
Background: Transcatheter edge-to-edge repair (TEER) of the mitral valve has emerged as an alternative treatment for mitral regurgitation (MR). However, the high radiation exposure during the process has been associated with multiple adverse effects for medical staff. In this study, we assessed the feasibility and safety of TEER performed solely under the echocardiographic (echo) guidance. Methods: Between April 2021 to August 2021, we retrospectively collected characteristics of 23 patients with MR who underwent TEER under echocardiographic guidance exclusively. Follow-up evaluations were performed at 1- , 3-months and 1-year post procedure. Results: All 23 patients (mean age, 66.1 ± 12.1 years; 65.2% males) successfully underwent echo-guided TEER, with 22 patients under transesophageal echo (TEE) guidance and 1 patient under transthoracic echo (TTE) guidance for severe esophageal stenosis. Of the patients, 60.9% received 1 implant and 39.1% received 2 implants. The median total procedural time was 130 (interquartile range, IQR: 90–150) min and the device procedure time was 73 (IQR: 58–100) min. The median length of stay was 6 (IQR: 5–9) days. At 3-months follow-up, 63.6% of patients had an MR ≤1+ and 90.9% had an MR ≤2+ (p < 0.001 vs. baseline). Improvement in functional status was observed, with 40.9% of patients classified as New York Heart Association (NYHA) functional class I and 45.5% as NYHA functional class II (p < 0.001 compared to baseline) at 3-months. At 1-year follow-up, 90.4% maintained MR reduction with MR ≤2+ (p < 0.001 vs. baseline). Single leaflet device attachment (SLDA) occurred in one patient (4.3%) 1-week post procedure. Conclusions: This retrospective, single-center, and pilot study demonstrates the feasibility, safety, and low complication rates of TEER guided solely by echocardiography. Our findings support the systematic use of echocardiography as the sole guidance modality for TEER, highlighting its potential as an alternative to fluoroscopy-guided procedures. Further multicenter and comparative studies are warranted to confirm these results and provide a more comprehensive evaluation of this approach.